USB-based radiation monitor - Drndarević Vujo; Jevtić Nenad; Đurić Radivoje (Nuclear Technology and Radiation Protection, 2006)
The Universal Serial Bus has become a dominant interface for the connection of standard peripheral devices to a PC computer. This paper analyzes the possibilities of USB bus applications in the field of measurement and environmental monitoring. As a result, a gamma radiation monitor consisting of an USB-based universal peripheral device and a gamma probe with a GM counter, has been designed. For the interfacing monitor with the powerful and easy to use LabVIEW software package, an instrument driver as a set of virtual instruments has been developed. The proposed monitor is a flexible instrument which can be used for laboratory measurements, as an environ mental radiation monitor or for training purposes. Connected to the laptop computer, the monitor becomes a portable instrument suitable for field measurements. Basic measurements and functionality properties of the radiation monitor are presented here.